Fibroblast Growth Factor 1 Promotes Rat Stem Leydig Cell Development - Chen, Lanlan; Li, Xiaoheng; Wang, Yiyan; Song, Tiantian; Li, Huitao; Xie, Lubin; Li, Linchao; Chen, Xianwu; Ma, Leikai; Chen, Yong; Lv, Yao; Li, Xingwang; et al. (Frontiers in Endocrinology, 2019)
Fibroblast growth factor 1 (FGF1) is reported to be expressed in the testis. How FGF1 affects stem Leydig cell development remains unclear. Here, we report the effects of FGF1 on rat stem Leydig cell development in an ethane dimethane sulfonate (EDS)-treated model. FGF1 (100 ng/testis) significantly increased serum testosterone level, increased PCNA-positive Leydig cell percentage and Leydig cell number, but down-regulated the expression of Lhcgr, Star, Cyp11a1, Hsd3b1, Cyp17a1, and Hsd11b1 in Leydig cells per se, after its daily intratesticular injection from post-EDS day 14 for 14 days. Primary culture of the seminiferous tubules showed that FGF1 stimulated EdU incorporation to stem Leydig cells but blocked the differentiation into the Leydig cell lineage, possibly via FGFR1-mediated mechanism. In conclusion, FGF1 promotes stem Leydig cell proliferation but blocks its differentiation.